The Interstitial Representation of Militaristic Masculinity in Amitav Ghosh’s Flood of Fire - Jayagopalan, Gaana (FRAME, Journal of Literary Studies, 2026)
This critical reading of Amitav Ghosh’s Flood of Fire (2015), the final instalment of the Ibis trilogy that fictionalises India’s role in the Opium Wars, evaluates the representation of imperial masculinities through the interpretive lens of cosmopolitan openness. Discourses of masculinity and soldierhood during nineteenth-century colonial India are closely analysed to explicate Ghosh’s representation of masculinity. Reading the militarized masculinity of the Indian sepoy Kesri Singh in the novel, configured by prevailing notions of hegemonic masculinity as a British soldier and a Rajput warrior, I argue here that positions of hegemonic masculinities are characterized by various anxieties, problematising cosmopolitan feelings and creating an ambivalent sense of openness to the Other.